POWER RELATIONS IN DEVELOPING BUSSINESS OF CATTLE FARM IN THE DISTRICT OF WEST TASIFETO, BELU REGENCY, INDONESIA’S EAST NUSA TENGGARA PROVINCE - Mbiri, Adeodata; Kushandajani, Kushandajani (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2020)
This research aims to analyze power relations between actors in developing local commodities through a cattle farm in the District of West Tasifeto, the Regency of Belu. The author applies descriptive qualitative research methods in disentangling power relations between actors who play their roles in drafting Belu?s Local Regulation (Peraturan Daerah/Perda) No. 6 of 2011. In collecting data, the author employs a qualitative approach, namely observation, and interviews with local farmers, Melus ethnic communities, Belu Regency?s government (Department of Farming Affairs), Local Businessmen, and secondary data from various documents. This study reveals that there are power relations among actors, namely local farmers, local authorities (Department of Farming Affairs, Belu Regency), and local businessmen, which are indicated by three indicators in drafting local regulation, selecting the farming area, and marketing the cattle products. Within these power relations, the actors influence each other at every moment and every connection. A strategy that is employed is not violence. Rather, it is through social relations and regulation system to promote various interests through politics of law, legal drafting, to enact a local regulation (Peraturan Daerah/Perda). Business people?s interests and political interests have been imposed in this process of extending local commodities, which compete with the local farmers? interests that less impacted by the government?s project. Therefore, the expansion of local commodities through a cattle farm in West Tasifeto results in the complexity of power relations interplaying with each other.